Hukum Poligami dan Interpretasi dalam Q.S. An-Nisa Ayat 3 - Aldin, Alfattiah (Sekolah Tinggi Ilmu Syariah Al-Hilal Sigli Aceh- Indonesia, 2023)
Polygamy in Surah An-Nisa ': 3 is a skill that is complicated and tightened. Polygamy is only allowed in an emergency and can only be done by people who really need it, while according to the system adopted by the Indonesian Marriage Law, the principle of monogamy is one husband for one wife. However, in certain cases or reasons, a husband is given permission to have more than one wife. This paper examines the regulation of polygamy regulated in Q.S. An-Nisa Paragraph 3 and Polygamy according to the applicable national law in Indonesia, namely Law Number 1 of 1974 concerning Marriage. Based on the results of the study, it shows that according to positive law in Indonesia, the court will only give permission to the husband to have more than one wife if there are special alternative causes, while in Islamic law it also does not require polygamy or recommend it, he only talks about the permissibility of polygamy, and that is also a small emergency exit. The Shari'a of the Qur'an, should not be viewed from the point of view of good and bad, but must be seen from the point of view of legal arrangements, in various conditions that may occur. There are many conditions other than those mentioned, which is also a logical reason not to close the door on polygamy.